FLIGHT LOAD MEASUREMENT CONSIDERING THE LOADING INSIDE STRAIN-GAGE STATION - ZHAO Yan; ZHOU ZhanTing; WAN XiaoPeng (Jixie qiangdu)
Aiming at virtual loads resulted from the loading inside strain-gage station,a method of considering the loading inside strain-gage station was given for flight load measurement based on superposition principle. Also the above method was applied to certain non-root flight load measurement,and the effects of the loading inside strain-gage station on load equation and measured flight load were discussed.